Rubber composition, and rubber product and hose using same

By using special carbon black and ether ester-based plasticizers within a specific range in polar rubber, the rubber composition is solved, and the tension property is reduced and the kneading processability is not achieved when the rubber reinforcement and resistance are improved in the prior art. The best problem achieves excellent high resistance and mechanical properties.

CN119403872APending Publication Date: 2025-02-07SUMITOMO RIKO CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280097322.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-27
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When the prior art improves the reinforcement and resistivity of polar rubbers such as acrylic rubber, it is easy to cause the rubber to be decreasing and the kneading processability is poor.

Method used

The rubber composition is formed by using a special carbon black with a ratio of the specific surface area of ​​nitrogen adsorption to the amount of iodine adsorption within a specific range, and combined with an ether ester plasticizer. The carbon black has high surfactivity, generates carbon gels, inhibits strong acid values, improves dispersion, and thus improves resistance and mechanical properties.

Benefits of technology

A rubber composition with high resistance, excellent mechanical properties and excellent kneading processability is achieved, and the problems of lowering rubber stretchability and poor kneading processability in the prior art are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005199446040000041
    Figure BDA0005199446040000041
  • Figure BDA0005199446040000121
    Figure BDA0005199446040000121
  • Figure BDA0005199446040000141
    Figure BDA0005199446040000141
Patent Text Reader

Abstract

Provided are: a rubber composition having high resistance, excellent mechanical properties, and excellent kneading processability; a rubber product using the rubber composition; and a hose. [Solution] A rubber composition containing a polar rubber as a main component and containing carbon black, the carbon black satisfying all the requirements represented by (a) to (d). (a) The ratio (N2SA / IA) of the nitrogen adsorption specific surface area (N2SA) to the iodine adsorption amount (IA) is 1.20 * 103 to 1.50 * 103 m2 / g. (b) The strongly acidic group concentration is 0.50 * 10 <-5 > mol / g or less. (c) The iodine adsorption amount (IA) is 50-70 mg / g. And (d) a DBP absorption amount of 130 to 150 cm < 3 > / 100 g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a rubber composition, a rubber product and a hose using the same, and more particularly to a rubber composition having both high reinforcement and high electrical resistance, and a rubber product and a hose using the same. Background Art

[0002] Conventionally, polar rubbers such as acrylic rubbers, which are used as materials for forming various rubber products such as hoses, contain fillers in order to improve mechanical properties such as reinforcement.

[0003] As the above-mentioned filler, carbon black is included in general fillers.

[0004] However, carbon black is not suitable for rubber products that require insulation due to its high conductivity.

[0005] Therefore, for example, as the above-mentioned filler, there is a filler in which non-conductive silica and carbon black are used together (Patent Document 1).

[0006] However, when silica is added to a polar rubber such as acrylic rubber, a problem of significant adhesion during the kneading process of the rubber is likely to occur due to the high or low surface activity of the silica.

[0007] In addition, the use of carbon black that is different from general carbon black and exhibits high electrical resistance is also being studied.

[0008] However, conventional high-resistance carbon black, that is, carbon black having a large surface area, also has a weak reinforcing property with respect to the rubber composition and further acts to reduce the viscosity of the rubber composition.

[0009] Therefore, it has been studied to use clay having low surface activity together with carbon black exhibiting high electrical resistance as described above, in order to achieve both improvement in electrical resistance and kneading processability (Patent Document 2).

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: International Publication No. 2020 / 017009

[0013] Patent Document 2: Japanese Patent Application Laid-Open No. 9-317956 Summary of the invention

[0014] Problems to be solved by the invention

[0015] However, when high-resistance carbon black and clay are used together with polar rubber such as acrylic rubber as shown in Patent Document 2, problems such as reduction in tensile properties of the rubber (TS, EB) occur, and a solution to this problem is desired.

[0016] The present invention has been made in view of the above circumstances, and provides a rubber composition having high electrical resistance, excellent mechanical properties, and excellent kneading processability, and a rubber product and a hose using the rubber composition.

[0017] Means used to solve problems

[0018] The inventors of the present invention have repeatedly conducted in-depth research to solve the above problems. In the course of their research, they explored the nitrogen adsorption specific surface area (N 2 The ratio of SA to iodine adsorption (IA) (N 2 Special carbon black having a specific range of SA / IA, strong acid group concentration, iodine adsorption (IA) and DBP absorption is added to polar rubber such as acrylic rubber.

[0019] The above special carbon black has high surface activity (high amount of functional groups on the surface of carbon black), so a lot of carbon gel is generated, and its strong acid value (amount of strongly acidic functional groups) is further suppressed, so it becomes easy to disperse in polar rubber, which contributes to high resistance and kneading processability. Furthermore, since the nitrogen adsorption value, which has a great influence on tensile properties, is large, it contributes to mechanical properties such as tensile properties.

[0020] Therefore, it was discovered that: as a filler material for a rubber composition with a polar rubber as a polymer, instead of using silica and clay as described above, the special carbon black mentioned above is used as a monomer, thereby achieving the kneading processability and mechanical properties (especially tensile properties) that are problems in the non-conductive design of the above-mentioned polar rubber at the same time.

[0021] That is, in order to achieve the above-mentioned object, the present invention is based on the following [1] to [8] as its gist.

[0022] [1] A rubber composition comprising a polar rubber as a main component and carbon black, wherein the carbon black satisfies all of the following requirements (a) to (d).

[0023] (a) Nitrogen adsorption specific surface area (N 2 The ratio of SA to iodine adsorption (IA) (N 2 SA / IA) is 1.20×10 3 ~1.50×10 3 m 2 / g.

[0024] (b) The concentration of strong acidic groups is 0.50×10 -5 mol / g or less.

[0025] (c) Iodine adsorption (IA) is 50 to 70 mg / g.

[0026] (d) DBP absorption is 130-150 cm 3 / 100g.

[0027] [2] The rubber composition according to [1], wherein the ratio of the carbon black to 100 parts by weight of the polar rubber is 30 to 100 parts by weight.

[0028] [3] The rubber composition according to [1] or [2], wherein the polar rubber is acrylic rubber.

[0029] [4] The rubber composition according to any one of [1] to [3], wherein the polar rubber has an SP value of 8.5 to 10.5.

[0030] [5] The rubber composition according to any one of [1] to [4], wherein the carbon black has a strong acid group concentration (b) of 0.30×10 -5 mol / g or less.

[0031] [6] The rubber composition according to any one of [1] to [5], further comprising an ether ester plasticizer.

[0032] [7] A rubber product, characterized in that the rubber product is composed of a cross-linked product of the rubber composition according to any one of [1] to [6].

[0033] [8] A hose comprising a cross-linked product of the rubber composition according to any one of [1] to [6].

[0034] Effects of the Invention

[0035] As described above, according to the present invention, a rubber composition having high electrical resistance, excellent mechanical properties, and excellent kneading processability, and a rubber product and a hose using the rubber composition can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic diagram showing the structure of a reactor for producing raw materials for carbon black. DETAILED DESCRIPTION

[0037] Next, an embodiment of the present invention will be described in detail. However, the present invention is not limited to this embodiment.

[0038] As described above, the rubber composition of the present invention is a rubber composition having polar rubber as a main component and containing carbon black, wherein the carbon black satisfies all the requirements (a) to (d) below.

[0039] (a) Nitrogen adsorption specific surface area (N 2 The ratio of SA to iodine adsorption (IA) (N 2 SA / IA) is 1.20×10 3 ~1.50×10 3 m 2 / g.

[0040] (b) The concentration of strong acidic groups is 0.50×10 -5 mol / g or less.

[0041] (c) Iodine adsorption (IA) is 50 to 70 mg / g.

[0042] (d) DBP absorption is 130-150 cm 3 / 100g.

[0043] [Polar rubber]

[0044] As described above, the rubber composition of the present invention has polar rubber as a main component. Here, the "main component" in the present invention generally refers to a component accounting for 30% by weight or more of the entire rubber composition, preferably a component accounting for 40 to 75% by weight of the entire rubber composition, and more preferably a component accounting for 45 to 60% by weight of the entire rubber composition.

[0045] The SP value of the polar rubber is preferably in the range of 8.5 to 10.5, more preferably in the range of 9 to 10, from the viewpoint of excellent dispersibility of the special carbon black.

[0046] Here, the SP value is also called a solubility parameter, is an index showing the polarity of a substance, and can be calculated by the following formula (1).

[0047] [Mathematical formula 1]

[0048]

[0049] In the above formula (1), ΔE represents evaporation energy, and V represents molar volume.

[0050] As the polar rubber, specifically, acrylic rubber, acrylonitrile butadiene rubber, chloroprene rubber, chlorosulfonated polyethylene rubber, epichlorohydrin rubber, etc. can be cited. They can be used alone or in combination of two or more. Among them, acrylic rubber is preferred from the aspect of excellent dispersibility of the special carbon black.

[0051] [Carbon black]

[0052] As described above, the carbon black used for the rubber composition of the present invention satisfies all the requirements shown in the following (a) to (d).

[0053] (a) Nitrogen adsorption specific surface area (N 2 The ratio of SA to iodine adsorption (IA) (N 2 SA / IA) is 1.20×10 3 ~1.50×10 3 m 2 / g.

[0054] (b) The concentration of strong acidic groups is 0.50×10 -5 mol / g or less.

[0055] (c) Iodine adsorption (IA) is 50 to 70 mg / g.

[0056] (d) DBP absorption is 130-150 cm 3 / 100g.

[0057] <Requirement (a)>

[0058] From the viewpoint of electrical insulation and mechanical properties in the rubber composition, the nitrogen adsorption specific surface area (N 2 The ratio of SA to iodine adsorption (IA) (N 2 SA / IA) needs to be set to 1.20×10 3 ~1.50×10 3 m 2 / g.

[0059] Here, N 2 SA is the specific surface area of ​​carbon black expressed by the amount of nitrogen molecules adsorbed per unit mass of carbon black (m 2 IA is a value expressed by the specific surface area of ​​carbon black as the amount of iodine molecules adsorbed per unit mass of carbon black in the liquid phase (mg / g).

[0060] The above N 2 SA is the same as IA above, which represents the specific surface area of ​​carbon black. IA is also a value that depends on the amount of surface functional groups of carbon black (the more acidic functional groups there are, the more difficult it is for iodine molecules to adsorb, and the more N 2 SA is slightly lower). 2 SA can be determined by the method described in JIS K 6217-7:2013 “Test methods for basic properties of carbon black for rubber use” (reference: ASTM D6556-16).

[0061] In addition, the above-mentioned IA is a value measured in accordance with JIS K 6217-1 (A method).

[0062] Use N 2 The value obtained by dividing the value of SA by the value of IA (N 2 SA / IA) is an index of the surface activity of carbon black. 2 The value of SA / IA is obtained by making N 2 The unit of SA is m 2 / g and the unit of IA is mg / g. 2 The larger the SA / IA value is, the more surface functional groups there are on the carbon black. When there are many surface functional groups on the carbon black, chemical reactions are likely to occur on the surface of the carbon black via the surface functional groups. In other words, the surface activity value of the carbon black is a value that quantitatively indicates the ease with which chemical reactions occur on the surface of the carbon black.

[0063] In addition, in order to balance the degree of adsorption to polar rubber molecules and the difficulty of carbon black coagulation, it is necessary not only to set the value of the strong acid group concentration of carbon black to be smaller than the predetermined value as shown in requirement (b), but also to set the amount of surface functional groups of carbon black to a predetermined range as shown in the above requirement (a). In other words, it is necessary to weigh the value of the strong acid group concentration and N 2 The value of SA / IA.

[0064] <Requirement (b)>

[0065] From the viewpoint of mechanical properties, electrical insulation, etc. in the rubber composition, the concentration of the strongly acidic group as the requirement (b) needs to be 0.50×10 -5 mol / g or less, and from the same viewpoint, preferably 0.30×10 - 5 mol / g or less, more preferably 0.10×10 -5 mol / g or less.

[0066] Here, the above-mentioned strong acid group concentration (mol / g) is a value expressing the amount of strongly acid groups (mainly carboxyl groups) present on the surface of carbon black as a substance amount per unit mass of carbon black.

[0067] Moreover, the carbon black used in the rubber composition of the present invention exhibits the above-mentioned strong acid group concentration, thereby improving the dispersibility of the carbon black in the polar rubber. As a result, the physical and chemical interactions between the carbon black surface and the molecular chains of the polar rubber are increased, which can further improve the mechanical strength of the rubber product composed of the rubber composition of the present invention.

[0068] Furthermore, as a result of the improved dispersibility of carbon black in the polar rubber, particles of carbon black are less likely to come into contact with each other, and thus the electrical insulation of the rubber composition and rubber product of the present invention is easily maintained.

[0069] Here, the above-mentioned strongly acidic group concentration can be measured by the following method.

[0070] That is, first, 5 g of a carbon black sample is accurately weighed and crushed, and 50 mL of a 0.1 mol / L sodium bicarbonate solution is added, and the mixture is shaken at room temperature for 4 hours to neutralize the strongly acidic functional groups on the surface of the carbon black. Afterwards, since it is known that there is no amount of remaining sodium bicarbonate for neutralization, 20 mL of the supernatant after filtering the carbon black by centrifugation is titrated with 0.025 mol / L sulfuric acid, and a blank test is performed in parallel (20 mL of 0.1 mol / L sodium bicarbonate of the original solution not used in the above reaction is titrated with 0.025 mol / L sulfuric acid), and the amount of strongly acidic functional groups per unit mass (mol / g) is calculated based on the difference between the two.

[0071] For example, according to the above measurement method, when the empty titration volume is 39.27 ml and the titration volume of the supernatant after the neutralization reaction is 39.25 ml, the difference between the two is 0.02 ml, so the concentration of strongly acidic groups can be calculated as 0.2×10 -5 mol / g.

[0072] <Requirement (c)>

[0073] From the viewpoint of mechanical properties, electrical insulation and the like in the rubber composition, the iodine adsorption amount (IA) as the requirement (c) needs to be 50 to 70 mg / g as described above.

[0074] In addition, as described above, the above IA is a value expressing the specific surface area of ​​carbon black by the amount of iodine molecules adsorbed per unit mass of carbon black in the liquid phase (mg / g). Moreover, by defining the lower limit of IA as described above, sufficient mechanical strength can be given to the rubber member. Furthermore, by defining the upper limit of IA as described above, high electrical insulation in the rubber composition and rubber product of the present invention can be maintained.

[0075] In addition, the above-mentioned IA is a value measured in accordance with JIS K 6217-1 (A method).

[0076] <Requirement (d)>

[0077] From the viewpoint of mechanical properties, electrical insulation, etc. in the rubber composition, the DBP absorption as the above requirement (d) needs to be 130 to 150 cm 3 / 100g.

[0078] The DBP absorption is the absorption of DBP (dibutyl phthalate) by the carbon black skeleton relative to 100g of carbon black (cm 3 The DBP absorption is a value measured in accordance with JIS K 6217-4.

[0079] The void ratio between carbon black aggregates is positively correlated with the carbon black framework. Therefore, the larger the DBP absorption value, the more developed the carbon black framework is, and adsorption or the proximity and contact of particles to each other are likely to occur. The lower limit of the above range is set for the DBP absorption value from the viewpoint of allowing carbon black to be well adsorbed to rubber molecules and imparting high mechanical strength to rubber components. Furthermore, the upper limit of the above range is set for the DBP absorption value from the viewpoint of preventing carbon black particles from approaching and contacting each other and maintaining high electrical insulation of rubber components.

[0080] From the viewpoints of mechanical properties, kneading processability, etc., the ratio of the above-mentioned special carbon black in the rubber composition of the present invention to 100 parts by weight of the polar rubber is preferably in the range of 30 to 100 parts by weight, more preferably in the range of 45 to 75 parts by weight, and further preferably in the range of 50 to 70 parts by weight.

[0081] 《Method for producing carbon black》

[0082] The above-mentioned special carbon black can be obtained by appropriately adjusting the reaction conditions in a general carbon black production method such as an oil furnace method. An example of a production method of the above-mentioned special carbon black will be described below.

[0083] The special carbon black used for the rubber composition of the present invention can be produced by, for example, performing the reaction step S1, the granulation step S2, the drying step S3, and the separation step S4 in this order.

[0084] <Reaction step S1>

[0085] In the above reaction step S1, for example, Figure 1 The reactor of the structure shown in the figure produces carbon black raw materials. As shown in the figure, the reactor is a cylindrical reactor, which includes a fuel combustion area 4, a raw material introduction area 6 and a reaction area 8.

[0086] The fuel combustion zone 4 in the above-mentioned reactor is a part that generates high-temperature combustion gas. An oxygen-containing gas inlet 1, a combustion burner 2, and an alkali metal salt aqueous solution supply nozzle 3 are provided in the fuel combustion zone 4. An oxygen-containing gas (oxygen, air, etc.) is introduced into the fuel combustion zone 4 from the oxygen-containing gas inlet 1. In addition, fuel (FCC residual oil, hydrogen, carbon monoxide, natural gas, petroleum gas, etc.) is supplied to the fuel combustion zone 4 from the combustion burner 2. Thus, a high-temperature combustion gas is generated. An aqueous solution of carbonates, chlorides, hydroxides, etc. such as sodium and potassium are supplied to the fuel combustion zone 4 from the alkali metal salt aqueous solution supply nozzle 3 as an alkali metal salt aqueous solution. By adding an alkali metal salt aqueous solution, it is possible to adjust so that the structure of carbon black is not developed in the raw material introduction zone 6. The combustion gas generated in the fuel combustion zone 4 is supplied to the raw material introduction zone 6.

[0087] In addition, the raw material introduction area 6 in the above-mentioned reactor is a part for introducing raw material oil. The diameter of the raw material introduction area 6 is smaller than the diameter of the fuel combustion area 4. A raw material oil introduction nozzle 5 is connected to the raw material introduction area 6. The raw material oil is introduced into the raw material introduction area 6 via the raw material oil introduction nozzle 5 and mixed with the combustion gas. At this time, tiny nuclei of carbon black are generated by thermal decomposition, and a predetermined framework is formed by the collision of the nuclei with each other, thereby generating carbon black particles as the raw material of carbon black. As the raw material oil, aromatic hydrocarbons such as naphthalene and anthracene, coal-based hydrocarbons such as creosote and tall oil, petroleum-based heavy oils such as FCC residual oil and ethylene heavy oil, acetylene-based unsaturated hydrocarbons, aliphatic hydrocarbons such as hexane, etc. can be used. The mixture of combustion gas and raw material oil is supplied to the reaction area 8.

[0088] Furthermore, the reaction area 8 in the above-mentioned reactor is a part where the reaction is stopped after the carbon black particles generated in the raw material introduction area 6 are further fully grown in the gas phase. The diameter of the reaction area 8 is larger than the diameter of the fuel combustion area 4. The flow rate of the carbon black particles generated in the raw material introduction area 6 becomes lower in the wide-diameter reaction area 8. At this time, the aromatic hydrocarbons in the gas phase are carbonized, stacked and grown on the surface of the carbon black particles to generate carbon black raw materials. A coolant introduction nozzle 7 for stopping the reaction is provided on the downstream side of the reaction area 8. Cooling water is sprayed from the coolant introduction nozzle 7 to the reaction area 8. As a result, the generation reaction of the carbon black raw material is stopped.

[0089] Furthermore, the carbon black raw material generated in the above-mentioned reaction zone 8 is moved to the capture system and captured by a capture device such as a separator and a bag filter.

[0090] <Granulation step S2>

[0091] In the above-mentioned granulation step S2, the carbon black raw material is granulated in such a manner that the particles of the carbon black raw material become a predetermined size. The carbon black raw material captured by the capture device is subjected to a granulation treatment. In the granulation treatment, that is, the carbon black particles are granulated in such a manner that they become a desired size. There is no particular limitation on the specific method of the granulation treatment, and a known granulation method can be applied. As a known granulation method, for example, a wet granulation method can be cited. An example of a wet granulation method is the following method: by rotating an axis having a plurality of special rod-shaped pins spirally arranged in the center of a cylinder at a high speed in a predetermined container, carbon and water are continuously supplied into the container, and they are stirred and mixed to granulate into a pellet shape of a predetermined size.

[0092] <Drying step S3>

[0093] In the above-mentioned drying step S3, in order to dehydrate the granulated carbon black raw material, the granulated carbon black raw material is dried to obtain a dry carbon black raw material. There is no particular limitation on the specific method of the drying process, and a known drying method can be applied. As a known drying method, for example, an indirect heating drying method can be cited. An example of an indirect heating drying method utilizes an indirect heating rotary dryer. It is a method in which hot gas is supplied to the space between the outer cylinder and the inner cylinder through a rotary furnace-shaped double tube structure of the indirect heating rotary dryer, and the granulated carbon black raw material containing water arranged in the inner cylinder is heated and dried at a predetermined temperature.

[0094] <Detaching step S4>

[0095] In the above-mentioned desorption step S4, only the strongly acidic groups are selectively desorbed and removed from the dry carbon black raw material to obtain carbon black. There is no particular limitation on the specific method of the desorption treatment, and any method that desorbs and removes the strongly acidic groups from the carbon black can be applied. As a particularly preferred desorption treatment method, for example, a heating treatment in an inert gas can be cited. An example of a heating treatment method in an inert gas is a method of heating the dry carbon black raw material at a temperature of 300 to 400° C. for 5 to 30 minutes while introducing an inert gas such as nitrogen into a fluidized bed in which the dry carbon black raw material is arranged.

[0096] The carbon black obtained by the above-mentioned production method can reduce the DBP absorption value by increasing the amount of the alkali metal salt aqueous solution introduced in the above-mentioned reaction step S1. If the amount of oxygen-containing gas introduced is increased or the amount of feedstock oil introduced is reduced, IA, N 2 In addition, if the reaction time from the introduction of the feedstock oil to the termination of the reaction by rapid cooling is further shortened, N 2 The value of SA / IA becomes larger.

[0097] In addition, in the above-mentioned desorption step S4, the degree of desorption of the strongly acidic group concentration can be adjusted by adjusting the temperature in the fluidized bed and the retention time in the fluidized bed.

[0098] [Other materials]

[0099] In the rubber composition of the present invention, in addition to the polar rubber and the above-mentioned special carbon black, a vulcanizing agent, a vulcanizing aid, a processing aid, a plasticizer, an anti-aging agent, a flame retardant, etc. are appropriately compounded. In addition, when cross-linking is performed using an organic peroxide, a co-cross-linking agent may also be used in combination in order to improve the cross-linking efficiency and improve the physical properties.

[0100] Examples of the vulcanizing agent include imidazole compounds such as 1-methylimidazole, 1,2-dimethylimidazole, 1-benzyl-2-methylimidazole, and 1-cyanoethyl-2-methylimidazole, hexamethylenediamine, hexamethylenediamine carbamate, tetramethylenepentamine, hexamethylenediamine-cinnamaldehyde adduct, ammonium benzoate, hexamethylenediamine dibenzoate, 4,4'-methylenedianiline, 4,4'-oxyphenyldiphenylamine, m-phenylenediamine, p-phenylenediamine, and 4,4'-methylenebis(o-chloroaniline). These may be used alone or in combination of two or more.

[0101] Examples of the vulcanization aid include trimethylthiourea, stearyltrimethylammonium bromide, di-o-tolylguanidine, etc. These may be used alone or in combination of two or more.

[0102] Examples of the processing aid include stearic acid, n-octadecylamine, polyoxyethylene stearyl ether phosphoric acid, etc. These can be used alone or in combination of two or more.

[0103] As the above-mentioned plasticizer, for example, polyether plasticizer, polyester plasticizer, ether ester plasticizer etc. can be listed. They can be used alone or in combination of two or more. Among them, from the aspect of excellent mechanical properties and cold resistance, ether ester plasticizer is preferably used, and adipic acid ether ester plasticizer is more preferably used.

[0104] Examples of the anti-aging agent include 4,4′-(α,α-dimethylbenzyl)diphenylamine, etc. These may be used alone or in combination of two or more.

[0105] Examples of the organic peroxide include 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclododecane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)octane, n-butyl-4,4-bis(tert-butylperoxy)octane, Peroxyketals such as butyl peroxide, n-butyl-4,4-bis(tert-butylperoxy)valerate, di-tert-butyl peroxide, diisopropyl benzene peroxide, tert-butyl isopropyl peroxide, α,α'-bis(tert-butylperoxym-isopropyl)benzene, α,α'-bis-(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne-3, etc. Oxides, acetyl peroxide, isobutyryl peroxide, octanoyl peroxide, decanoyl peroxide, lauroyl peroxide, 3,5,5-trimethylhexanoyl peroxide, benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, m-tritoluoyl peroxide and other diacyl peroxides, tert-butyl peroxyacetate, tert-butyl peroxyisobutyrate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxylaurate, peroxy Peroxyesters such as tert-butyl benzoate, di-tert-butyl peroxyisophthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butyl peroxymaleate, tert-butyl peroxyisopropyl carbonate, and cumyl peroxyoctanoate, and hydroperoxides such as tert-butyl hydroperoxide, cumyl hydroperoxide, diisopropylphenyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide and 1,1,3,3-tetramethylbutyl peroxide, etc. These may be used alone or in combination of two or more.

[0106] Examples of the co-crosslinking agent include sulfur-containing compounds, polyfunctional monomers, maleimide compounds, and quinone compounds, etc. These can be used alone or in combination of two or more.

[0107] As the above-mentioned sulfur-containing compound, for example, sulfur, tetrasulfide dipentamethylenethiuram, mercaptobenzothiazole, etc. can be cited. As the above-mentioned multifunctional monomer, for example, divinylbenzene, ethylene glycol dimethacrylate, diallyl phthalate, trimethylolpropane trimethacrylate, triallyl cyanurate, triallyl isocyanurate (TAIC), triallyl trimellitate, triallyl tricyanurate, etc. can be cited. In addition, as the above-mentioned maleimide compound, for example, N, N'-m-phenylene bismaleimide, tolyl bismaleimide, etc. can be cited. As the above-mentioned quinone compound, for example, quinone dioxime, dibenzoyl quinone dioxime, etc. can be cited.

[0108] The rubber composition of the present invention can be prepared by, for example, mixing polar rubber, specific carbon black, and further appropriately mixing vulcanizing agents, vulcanizing aids, processing aids, plasticizers, antioxidants, flame retardants, etc., and kneading them using a mixer such as a roll, a kneader, or a Banbury mixer.

[0109] The rubber composition of the present invention thus obtained has high electrical resistance and is excellent in mechanical properties, and is also excellent in kneading processability during kneading in the above-mentioned kneading machine.

[0110] Then, by cross-linking the rubber composition into a predetermined shape using a mold or the like as necessary, a target rubber product can be produced.

[0111] Since the rubber composition is excellent in kneading processability, the rubber product is excellent in moldability, and further has high electrical resistance and excellent mechanical properties.

[0112] Examples of the rubber product include hoses and gaskets.

[0113] Here, as an example of a method for producing a rubber product using the rubber composition described above, a method for producing a hose will be described below.

[0114] That is, first, after preparing the rubber composition as described above, the rubber composition is extruded into a tubular (cylindrical) shape to form an uncrosslinked rubber layer. In addition, in the case of a multi-layer hose, a layer composed of various rubbers and resins is formed on the periphery of the rubber layer (innermost layer) by extrusion molding or the like. In addition, in the case of forming a reinforcing yarn layer, the reinforcing yarn is braided and woven with a predetermined number of pulls and punches relative to the periphery of the rubber layer (innermost layer) to form a reinforcing yarn layer. A mandrel is inserted into the uncrosslinked hose structure thus obtained. In addition, as required, a mold release agent such as a silicone oil system can also be applied to the surface of the mandrel. In addition, as described above, the mandrel can be directly extruded on the mandrel instead of inserting the mandrel into the uncrosslinked hose structure (uncrosslinked rubber hose). Then, the uncrosslinked rubber hose extruded on the mandrel is crosslinked by pressurized steam, and the mandrel is pulled out, and further, secondary crosslinking is performed in an oven as required, thereby making the target hose.

[0115] The hose thus obtained may be a single-layer structure or a multi-layer structure in which two or more layers are stacked, without particular limitation. From the viewpoint of preventing damage to the hose due to static electricity generated by the fluid flowing inside the hose, corrosion of a joint connected to the hose, etc., it is preferred that at least the innermost layer (the layer in the case of a single-layer structure) be composed of the rubber composition.

[0116] In the hose of the present invention obtained as described above, the thickness of the innermost layer (in the case of a single-layer structure, this layer) is preferably 0.25 to 20 mm, more preferably 0.5 to 10 mm. The inner diameter of the hose is preferably 2 to 100 mm, more preferably 5 to 70 mm.

[0117] The hose of the present invention is not particularly limited and can be preferably used for all hoses requiring heat resistance. More preferably, it can be used for heat-resistant hoses requiring high electrical resistance, such as oil hoses such as oil cooler hoses for automatic transmissions (AT, CVT) in transporters such as automobiles, and air hoses such as turbo air hoses.

[0118] Example

[0119] Next, examples will be described together with comparative examples, but the present invention is not limited to these examples unless the gist of the present invention is exceeded.

[0120] First, before the examples and comparative examples, N 2 SA / IA(×10 3 m 2 / g), strong acid group concentration (×10 -5 mol / g), IA (mg / g) and DBP absorption (cm 3 In addition, the above-mentioned physical property values ​​are measured according to the above-mentioned measurement methods.

[0121] Here, the carbon black (1) to the carbon black (6) are produced by sequentially performing the reaction step S1, the granulation step S2, the drying step S3 and the separation step S4 in this order. That is, first, in the reaction step S1, the amount of fuel supplied, the amount of feedstock oil introduced, the amount of air supplied, the reaction time from the introduction of feedstock oil to the termination of the reaction by rapid cooling, and the amount of alkali metal salt aqueous solution introduced are changed using the reaction furnace to generate five kinds of carbon black raw materials with different properties, and then in the granulation step S2, wet granulation treatment is performed under certain conditions, and then in the separation step S4, the granulated carbon black raw material is dried under certain conditions using an indirect heating type rotary dryer, and in the separation step S4, the dry carbon black raw material is arranged in a fluidized bed heated to 350°C, and the dry carbon black raw material is retained for 10 minutes while nitrogen gas is introduced into the fluidized bed, thereby producing the carbon black (1) to the carbon black (6).

[0122] In addition, in the manufacture of carbon black (7) to carbon black (12), the above-mentioned separation step S4 is not carried out, but the other steps are carried out in accordance with the manufacturing method of the above-mentioned carbon black (1) to carbon black (6). By changing the fuel supply amount, the introduction amount of raw oil, the air supply amount, the reaction time from the introduction of the raw oil to the termination of the reaction by rapid cooling, and the introduction amount of the alkali metal salt aqueous solution in the above-mentioned reaction step S1, carbon black (7) to carbon black (12) with different properties are manufactured.

[0123] [Table 1]

[0124]

[0125] [Example 1]

[0126] After kneading 100 parts by weight of polar rubber (1) (trade name: DENKA ER8401, manufactured by DENKA Corporation, SP value: 9.4), 60 parts by weight of the above carbon black (1), 15 parts by weight of plasticizer (1) (adipate ether ester plasticizer (ADK CIZER RS-107, manufactured by ADEKA Corporation)), 2 parts by weight of liquid paraffin (trade name: liquid paraffin 70S, manufactured by Sanko Chemical Co., Ltd.), 2 parts by weight of stearic acid (trade name: Lunac S-30, manufactured by Kao Corporation), 2 parts by weight of antioxidant (trade name: Naugard 445, manufactured by Crompton Corporation), 0.75 parts by weight of imidazole compound (trade name: 2MZ-CN, manufactured by Shikoku Chemical Industry Co., Ltd.), and 1 part by weight of sodium lauryl sulfate (trade name: EMAAR 2FG, manufactured by Kao Corporation) using a 5L kneader, the mixture was transferred to an open roll and kneading was continued to prepare a rubber composition. Next, the rubber composition was press-formed into a rubber sheet having a thickness of 2 mm for measuring tensile properties using a press vulcanizer, thereby producing a vulcanized rubber sheet.

[0127] [Example 2 to Example 11, Comparative Example 1 to Comparative Example 8]

[0128] The type of polar rubber, the type and ratio of carbon black (ratio relative to 100 parts by weight of polar rubber), and the type of plasticizer were as shown in the following Tables 2 and 3. A rubber composition was prepared in the same manner as in Example 1 except for the above.

[0129] The polar rubber (2) described in Tables 2 and 3 below is trade name: Nipol DN401 (manufactured by Zeon, SP value: 8.9), and the polar rubber (3) is trade name: EPICHLOMER CG105 (manufactured by OSAKA SODA, SP value: 9.8).

[0130] In addition, the types of carbon black described in Table 2 and Table 3 (carbon black (1) to carbon black (12)) are as shown in Table 1 above.

[0131] The carbon black (13) of Comparative Example 7 in Table 3 is Niteron #10N (IA: 41 mg / g, N 2 SA: 41m 2 / g, DBP absorption 121cm 3 / 100g).

[0132] The plasticizer (2) described in Tables 2 and 3 below is di(2-ethylhexyl) phthalate (manufactured by Daihachi Chemical Industry Co., Ltd.), the silica is ULTRASIL VN3 (manufactured by Evonik), and the clay is kaolin clay (manufactured by Takehara Chemical Industry Co., Ltd.).

[0133] The rubber compositions of Examples and Comparative Examples obtained in this manner were used to evaluate various properties according to the following criteria. The results are shown together in Tables 2 and 3 described below.

[0134] Stretching Properties

[0135] The tensile strength TS (MPa) and elongation EB (%) of the sample obtained by crosslinking the rubber composition were measured according to JIS K 6251-2017 (Vulcanized rubber and thermoplastic rubber - Calculation method of tensile properties). Then, the tensile strength and elongation were evaluated according to the following criteria.

[0136] ○ (very good): tensile strength TS is 8.0 MPa or more and elongation EB is 170% or more

[0137] × (poor): At least one of the tensile strength TS and the elongation EB does not satisfy the standard of "0 (very good)"

[0138] Volume resistivity

[0139] The volume resistivity VR (Ω·cm) of a sample obtained by crosslinking the rubber composition was measured in accordance with JIS K 6271-1:2015 (vulcanized rubber and thermoplastic rubber—method for calculating resistivity).

[0140] Specifically, the volume resistivity VR was determined under the following conditions.

[0141] Determination method: double ring electrode method

[0142] Guard electrode: outer diameter 80mm, inner diameter 70mm

[0143] Main electrode: 50mm

[0144] Sample outer dimensions: 100mm×100mm

[0145] Sample thickness: 2mm

[0146] Applied voltage: 1V

[0147] Detection current range: 200pA~20mA

[0148] Then, the volume resistivity VR was evaluated according to the following criteria.

[0149] ○ (very good): Volume resistivity LogVR is 5.5Ω·cm or more

[0150] × (bad): The volume resistivity LogVR is less than 5.5·cm.

[0151] 《Kneading processability》

[0152] During the kneading operation using an open roll when preparing the rubber composition, whether or not adhesion occurred between the roll and the rubber was visually evaluated based on the following criteria.

[0153] ○ (very good): No adhesion between roller / rubber

[0154] × (bad): Adhesion occurs between the roller and rubber

[0155] [Table 2]

[0156]

[0157] [Table 3]

[0158]

[0159] From the above results, the rubber compositions of Examples were evaluated to have high tensile strength and high volume resistivity, and to have high electrical resistance and excellent kneading processability.

[0160] In contrast, the rubber compositions of the comparative examples do not use carbon black satisfying the requirements of the present invention, and cannot satisfy all the properties (tensile strength, volume resistivity, kneading processability) required by the present invention as the rubber compositions of the examples do.

[0161] In Comparative Example 7, although high electrical resistance was achieved by adding silica to carbon black (carbon black (13)) having high electrical conductivity, the kneading processability was poor. In Comparative Example 8, although clay was added to carbon black (carbon black (8)) having high electrical resistance, the kneading processability was improved, but the tensile strength was poor.

[0162] In the above embodiments, specific modes of the present invention are shown, but the above embodiments are only examples and are not to be interpreted as limiting. Various modifications obvious to those skilled in the art are also intended to fall within the scope of the present invention.

[0163] Industrial Applicability

[0164] The rubber composition of the present invention is used as a material for various rubber products such as hoses and gaskets. It is preferably used as a material for forming the innermost layer of an oil cooler hose for an automatic transmission (AT, CVT) for a motor vehicle, a turbo air hose for a motor vehicle, etc. Moreover, these hoses are preferably used for transporters such as motor vehicles, tractors, tillers, and ships.

[0165] Description of reference numerals:

[0166] 1: oxygen-containing gas inlet;

[0167] 2: Burner for combustion;

[0168] 3: Alkali metal salt aqueous solution supply nozzle;

[0169] 4: fuel combustion area;

[0170] 5: Raw oil introduction nozzle;

[0171] 6: Raw material import area;

[0172] 7: Coolant introduction nozzle;

[0173] 8: Reaction area.

Claims

1. A rubber composition comprising polar rubber as a main component and carbon black, characterized in that: The carbon black satisfies all of the following requirements (a) to (d): (a) The ratio of nitrogen adsorption specific surface area (N2SA) to iodine adsorption (IA) (N2SA / IA) is 1.20×10 3 ~1.50×10 3 m 2 / g, (b) The concentration of strong acidic groups is 0.50×10 -5 mol / g or less, (c) Iodine adsorption (IA) is 50-70 mg / g, (d) DBP absorption is 130-150 cm 3 / 100g.

2. The rubber composition according to claim 1, characterized in that The ratio of the carbon black to 100 parts by weight of the polar rubber is 30 to 100 parts by weight.

3. The rubber composition according to claim 1 or 2, characterized in that: The polar rubber is acrylic rubber.

4. The rubber composition according to any one of claims 1 to 3, characterized in that The polar rubber has an SP value of 8.5 to 10.

5.

5. The rubber composition according to any one of claims 1 to 4, characterized in that The strong acid group concentration (b) of the carbon black is 0.30×10 -5 mol / g or less.

6. The rubber composition according to any one of claims 1 to 5, characterized in that The rubber composition further contains an ether ester plasticizer.

7. A rubber product, characterized in that: The rubber product is composed of a cross-linked product of the rubber composition according to any one of claims 1 to 6.

8. A hose, characterized in that: The hose is composed of a cross-linked product of the rubber composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Vehicular cooling liquid transport hose

    JP1997317956A

  • Rubber composition for hose

    WO2020017009A1